Biogeographic Atlas of the Deep NW Pacific Fauna - Hanieh Saeedi (Pensoft Publishers, 2020)
Experts in deep-sea taxonomy and ecology have worked together for four Russian-German and German-Russian expeditions in the NW Pacific deep sea (Sea of Japan, Sea of Okhotsk, Kuril-Kamchatka abyssal plain and the Kuril-Kamchatka Trench). This book provides a summary of the findings of these experts following the many hours of subsequent sample-processing and analyses, revealing a treasure trove of critical fundamental knowledge of life in our deep oceans.